2016
DOI: 10.1515/plm-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for cancer of the pancreas – The story so far

Abstract: Pancreatic cancer has long been a leading cause of cancer death. Few patients are suitable for surgery and for those who are not, the response to treatment is generally poor. No more than about 10% survive for more than a year. Recent research has focused on focal treatment for local disease control. This review covers the development of one of the most promising options, photodynamic therapy (PDT).This review covers pre-clinical and clinical studies. Laboratory work was designed to understand the effect of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Furthermore, they highlighted that the combination of various treatments (including targeted, immunotherapy, or cannabidiol) might be a justified strategy for colorectal cancer treatment. PDT has proved a possible option for minimally invasive treatment for the pancreas, but it is still at an early stage of development [36]. In Ref.…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…Furthermore, they highlighted that the combination of various treatments (including targeted, immunotherapy, or cannabidiol) might be a justified strategy for colorectal cancer treatment. PDT has proved a possible option for minimally invasive treatment for the pancreas, but it is still at an early stage of development [36]. In Ref.…”
Section: Gastrointestinal Cancermentioning
confidence: 99%
“…Results obtained in PC-3 cells, demonstrated that the catalyst-substrate pair Rf/39 was not toxic in the dark, while upon blue light irradiation cell viability was reduced to values comparable to cisplatin. On the other hand, Capan-1 cells were tested because they showed high tolerance against singlet oxygen damaging [86][87][88]. Viability experiments in this cell line suggested that the pair (Rf/39) was also effective under regimes in which PDT was not effective, because of the selective photocatalytic activation of the Pt IV substrate [89].…”
Section: Figure 14mentioning
confidence: 99%
“…Photodynamic therapy (PDT) is employed to treat a variety of skin diseases (such as actinic keratosis, basal cell carcinoma, and psoriatic plaque) [1][2][3][4] cancers (of the lung, bladder, colon, prostate, gastrointestinal, pancreatic, and breast), and fungal infections [5][6][7][8][9][10][11]. In PDT, exposure to light of the appropriate wavelength (400-700 nm) alters the conformation of a photosensitizer molecule, generating radicals and/or reactive oxygen species (ROS) that destroy the target cells [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%